Bio-engineering of 3-D cell sheets for diabetic rats: Interaction between mesenchymal stem cells and beta cells in functional islet regeneration system. (December 2022) - Duman, Busra Oncel; Sariboyaci, Ayla Eker; Karaoz, Erdal
Abstract: Type 1 diabetes is an autoimmune disease that emerges with the destruction of beta cells of pancreatic Langerhans islets. Three different therapeutical approaches have been developed so far; pancreas transplantation, islet transplantation, and cell-based therapies. Bioengineering cell sheets for tissue generating is one of the latest approaches that have been used to construct cell-sheets instead of single cells so that it mimics the in vivo environments more. In this study, extra-hepatic functional islet tissue was constructed by transferring the 3-D beta cells and GFP labelled MSCs MSC sheets to the subcutaneous site of rats with STZ-induced diabetes. rBM-MSCs and beta cells were cultured on the 6-well PIPAAm culture dishes. Obtained rBM-MSCs as two-cell sheets and beta cells cultured in droplets with matrigel has transplanted into the dorsal subcutaneous area of diabetic rats. Fasting blood glucose levels and body weights were evaluated for 30 days after transplantation. Immunocytochemistry analysis for the anti-apoptotic, anti-inflammatory, and angiogenetic effects of MSCs on the 30th day of subcutaneous cell transplantation. All recipient rats transplanted with beta-cells with MSCs returned toward normoglycemia by day 5 and remained at this level for 30 days. Immunocytochemical analyses supported that the MSCs and beta cells preserved their viability and function. MSCs secrete cytokines and growth factors TGF-β and IL-6; MSCs of the important features of the anti-apoptotic and anti-inflammatory properties, thanks to apoptosis of beta cells preserve graft explained by inhibition. In transplantation of MSCs induced angiogenesis and neovascularization, PECAM-1 and GFP positive simultaneously determining endothelial cells was observed indicating. Subcutaneous 3D beta-cell transplantation would be possible with the MSC-sheets as a feeder layer of beta cells. The beta-cell line is glucose-sensitive and has a high insulin release potential, and can be used as an alternative to islets in in vivo transplant studies. Graphical Abstract: ga1 Highlights: 3D beta cell-MSC sheets return diabetic rats toward normoglycemia. MSCs induce anti-apoptotic, anti-inflammatory and angiogenetic effects in the subcutaneously transplanted grafts. Immunocytochemical analyses supports that the MSCs and beta cells preserves their viability and function in transplanted grafts. Subcutaneous 3D beta-cell transplantation is possible clinically with the MSC-sheets as a feeder layer of beta cells.